Przez Atlantę do Rio – Letnie Igrzyska Olimpijskie w TVP "wczoraj" i "dziś" - Janik, Mariusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Ever since the 60’s the Telewizja Polska takes the duty of broadcasting the Olympics in Poland. Almost everytime a few channels from Telewizja Polska take part in it by offering hundreds of hours full of live transmissions from the Olympics, talks with guests in the Studia Olimpijskie, exclusive interviews, etc. Historical part when it comes to broadcasting were the Olympics in Rio in 2016. TVP had given its receivers over 800 hours of direct transmissions. Additionally, thanks to the websites and apps we were given transmissions of many other disciplines - the viewer could decide which discipline he wants to watch thanks to the broad offer from TVP. The paper is going to focus on the changes that took place within the 20 years of Olympics broadcasts in polish television. Since we are on topic, it’s worthwhile to take a second to think what kind of technology will have its debut during the Olympics in Tokio in 2020.